Site-specific sediment responses to climate change during the last 140 years in three varved lakes in Northern Poland. (March 2018) - Ott, Florian; Kramkowski, Mateusz; Wulf, Sabine; Plessen, Birgit; Serb, Johanna; Tjallingii, Rik; Schwab, Markus; Słowiński, Michał; Brykała, Dariusz; Tyszkowski, Sebastian; Putyrskaya, Victoria; Appelt, Oona; et al.
Accurate dating and unambiguous chronological correlation using cryptotephras provide a powerful tool to compare the varved sediment records of the lakes Głęboczek (JG), Czechowskie (JC) and Jelonek (JEL) (north-central Poland). For the last 140 years, micro-facies analyses and µ-XRF element scanning at seasonal resolution, as well as bulk elemental analyses (organic matter, carbonate) at sub-decadal to decadal resolution, were conducted for all three lakes records. All lakes are located in a region with low population density, and therefore, anthropogenic influences are negligible or only minor. The varve chronologies have been established independently for each record and were synchronized with the Askja AD 1875 cryptotephra. Comparison with monthly temperature data since 1870 and daily temperature data since 1951 revealed different responses of lake deposition to recent climate change. Varves are well preserved over the entire 140 years only at JG, while in the JC record two faintly varved intervals are intercalated and in the JEL record two non-varved intervals occur at the base and top of the profiles. These differences likely are due to variations in lake characteristics and their influence on lake-internal responses. JG is the smallest and best wind-sheltered lake, which favours varve preservation. JC's attenuated sediment responses can likely be linked to lake productivity changes with respect to climate warming. JEL is lacking a direct sedimentological response to the observed temperature increase, which can be linked to lake size and water depth superimposing regional climate changes. Climate changes at the demise of the 'Little Ice Age' around 1900 and the recent warming since the 1980s are expressed in sediment proxies in the lakes with different response times and amplitudes. This detailed comparison study on three nearby lakes demonstrates the influence of local parameters such as lake and catchment size and water depth superimposed on more regional climate-driven changes.